Seven steps to a comprehensive literature review : a multimodal and cultural approach - Onwuegbuzie, Anthony J.; Frels, Rebecca K. (Thousand Oaks, Los Angeles, California, USA : Sage Publications Ltd., 2016)
With a key focus on mixed methods, coverage of the 'why' as well as the 'how', and clear explanation of the CORE system, this book will be instrumental in helping readers to produce organized, ethical, insightful and, of course, comprehensive literature reviews
PART ONE: OVERVIEW Chapter 1: Foundations of the Literature Review Chapter 2: The Literature Review Chapter 3: Methodology of the Literature Review PART TWO: EXPLORATION Chapter 4: Step 1: Exploring Beliefs and Topics Chapter 5: Step 2: Initiating the Search Chapter 6: Step 3: Storing and Organizing Information Chapter 7: Step 4: Selecting/Deselecting Information Chapter 8: Step 5: Expanding the Search: Media, Observation(s), Documents, Experts and Secondary Data PART THREE: INTEGRATION Chapter 9: Step 6: Analyzing and Synthesizing Information PART FOUR: COMMUNICATION Chapter 10: Step 7: Presenting the CLR Report: Planning Phase Chapter 11: Step 7: Presenting the CLR Written Report APPENDICES Appendix A: Supplemental Tables of Quantitative, Qualitative, and Mixed Research Designs Appendix B: Quantitative, Qualitative, and Mixed Legitimation Frameworks
Includes bibliographical references and index.
Keywords: Research -- Methodology